Spatial integration of property close recycling - Palmlöf, Kristina (My University, 2025)
The health of the planet is declining rapidly, and we are depleting nature's capital faster than it can regenerate. To save our environment, a transformative shift in society is urgently needed. Sweden has traditionally played a leading role in waste management, but despite the progress, recycling has become increasingly challenging due to higher ambitious targets in the European Union (EU). To attempt to meet the new goals Sweden is currently in the process of implementing a new law, which mandates that by January 1, 2027, all households and co-located businesses must have “property-close recycling”. It means that after 2027, residents can no longer be directed to recycle their packaging waste (paper, plastic, metal, and colored or clear glass) at a public recycling station, but should instead be able to do so from, or near, their property. The new rules aim to make it easier to sort packaging waste and to counteract poor waste management. Implementing property-close recycling presents challenges. The thesis is an examination of the spatial consequences that may arise with the new law on property-close recycling, as well as proposals for solutions that address the challenges from an architectural perspective and promote sustainable resource management. Through an iterative process based on research and design, the thesis examines three specific areas in Gothenburg: Robertshöjd, Haga, and Brännö. Where the implementation of the new legislation presents various challenges. The result is three different design proposals, grounded in circular economy principles, nudging theory and gathered data. These proposals illustrate how recycling spaces can evolve beyond just functional areas. By incorporating additional features and creating inviting environments, these spaces can become places where engaging with the waste hierarchy feels more intuitive and natural. The potential for spontaneous interactions and a sense of community can transform recycling from a task into an asset. By highlighting the architectural perspective in waste management, the thesis aims to demonstrate how the architect’s role can contribute to making recycling easier and counteracting unsustainable resource management.